Peran Bumdes Dalam Meningkatkan Kesejahteraan Masyarakat Menurut Perspektif Ekonomi Islam - Irmayanti, Adek; Hakim, Andy; Lubis, Muhlisah (Studia Economica : Jurnal Ekonomi Islam, 2024)
This research was carried out on the basis of describing the Role of Village-Owned Enterprises (BUMDes) in improving community welfare according to the perspective of Islamic economics (Case study on BUMDes Sibanggor Jae mineral water. The reason for taking the case study was in Sibanggor Jae Village, Puncak Sorik Marapi District, Mandailing Natal Regency, which is one of the villages that operate BUMDes. This research was conducted from October 2023 to July 2024. This research method uses a qualitative approach where this research describes and explains and interprets the object as it is. Data validation was carried out by digging information from several informants directly related to the Mineral Water BUMDes.  In addition, the researcher also made direct observations at the research location to verify the data to compare the data obtained from the informants in line with the data or different. As a result of this study, the author concludes that the role of BUMDes